Strategi Pencegahan Pemberantasan Penyalahgunaan Dan Peredaran Gelap Narkotika (P4GN) - Suroso Suroso (Universitas Islam Kadiri, 2020)
The research was distributed by worries researchers about the abuse and illicit traffic in narcotics in Tulungagung district. The high cases of abuse of and illicit traffic in narcotic drugs of concern for the Government which is also very seized public attention in Tulungagung district. Even considering its importance, the Government called for a State of emergency drugs. Therefore, the strategy of the National Narcotics Agency Tulungagung district in the prevention and eradication of misuse and illicit narcotics is highly expected to overcome the problem of narcotic drugs in accordance with the provisions of Law No. 35 of the year 2009 about narcotics. The methods used in this research is qualitative research method with descriptive analysis approach. The purpose of this research is to analyze how the strategy of the National Narcotics Agency Tulungagung district in the prevention and eradication of abuse and illicit traffic in narcotic drugs (P4GN) in Tulungagung district. The type of research that is used is the type of research that is descriptive qualitative research i.e. expose the description of circumstances that occur in field. This research was carried out at the Office of the National Narcotics Agency Tulungagung district. Source data obtained by using a Purposive Sampling method where that becomes Key Informants is the head of BNNK Tulungagung, whereas Section prevention and community empowerment and the eradication of Section as well as the General Head of sub-division as the informant. The research results obtained from portrayal of the National Narcotics Agency strategy that Tulungagung district in the field of the prevention and eradication of misuse and illicit narcotics in Tulungagung district has yet to run a maximum of due at least power extension officers of the anti drugs certified extension officers resulting in less professional in carrying out basic tasks and functions. Whereas in the field of the eradication of the maximum because not all members of the section the eradication has not followed a psychological test as a condition of holding the weapon so far in carrying out the activities of the operations have not been supported with weaponry. In order to optimize the prevention and eradication of abuse and illicit traffic in narcotic drugs (P4GN) in Tulungagung, Tulungagung district BNN then needs to evaluate the strategies currently being implemented growth strategy and stability (horizontal integration) and correct the weaknesses and take advantage of opportunities to overcome the threats so Tulungagung district free from abuse and illicit traffic in narcotics